Oxidation of Residual Lipids in Fish Protein Concentrates and its Effect on the Nutritional Quality of the Protein - DEVADASAN, K (Fishery Technology, 2017)
The paper reviews the work reported on the changes in the nutritive value of fish protein concentrates (FPC) during, storage, with special emphasis on the effects of the interactions between oxidised residual lipids and proteins of the FPC. Theories on the oxidised lipid-protein interactions are reviewed and the nutritional significance of these reactions is discussed.